Dealing with the Vocabulary Difficulties of BSED English Students in Reading Literary Texts - Alexa Claro; Dion Paolo Lamosao; Glaidyn Abijay; Aris Pet Angeli Suarez; Genesis Naparan (Journal of English as A Foreign Language Teaching and Research, 2025)
Vocabulary Difficulties are words that BSED English students commonly encounter when reading literary texts, particularly in literature subjects. These difficulties can significantly impede students' comprehension and interpretation of various scholarly works. This study employs the Merriam Case Study Model from 1998 since it aims to provide a contextualized understanding of the vocabulary difficulties faced by BSED English students in reading literary texts. This research employed a triangulation method to collect data from fifteen fourth-year BSED English students, as well as from two peers and two English teachers, using a semi-structured interview guide. The findings highlight the students' perceptions regarding the importance of vocabulary in their reading experiences. Key findings revealed that vocabulary mastery facilitates interpretation, evokes epistemic emotions, and fosters audience engagement. However, students reported several vocabulary difficulties, including encountering unfamiliar words, misusing words, and spelling problems. To address these vocabulary difficulties, BSED English students employed various strategies, such as searching for information, expanding vocabulary through reading, note-taking words, utilizing AI tools, and identifying context clues. Additionally, students expressed intentions or plans to improve their vocabulary by maintaining vocabulary-building notes, reading engagement, participating in English-speaking practices, and immersing in gamification. In conclusion, this study is significant to the body of knowledge and in theoretical and practical methods for both BSED English learners and literature teachers. The study presents several recommendations to enhance teaching and learning strategies within literature courses to better support students in dealing with vocabulary difficulties in literature classes.